The Occurrence of Acute Disseminated Encephalomyelitis in SARS-CoV-2 Infection/Vaccination: Our Experience and a Systematic Review of the Literature - Adina Stoian; Zoltan Bajko; Mircea Stoian; Roxana Adriana Cioflinc; Raluca Niculescu; Emil Marian Arbănași; Eliza Russu; Marian Botoncea; Rodica Bălașa (Vaccines, 2023)
Background: The neurological complications of coronavirus disease 2019 (COVID-19) infection and the side effects of vaccination include immune-mediated diseases of the central nervous system (CNS) such as acute disseminated encephalomyelitis (ADEM). It is an acute-onset demyelinating disease that involves a rapid evolution and multifocal neurological deficits that develops following a viral or bacterial infection or, less frequently, following vaccination. Acute hemorrhagic leukoencephalitis (AHLE) is the hemorrhagic variant of ADEM that presents a more severe evolution which can be followed by coma and death. The objectives of this study consist in evaluating the diagnosis, clinical characteristics, imaging and laboratory features, evolution, and treatment of ADEM and AHLE following COVID-19 infection or vaccination. Methods: We performed a systematic review of the medical literature according to PRISMA guidelines that included ADEM cases published between 1 January 2020 and 30 November 2022 following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and vaccination and also included our own clinical experience regarding this pathology. Results: A total number of 74 patients were diagnosed with ADEM, 45 following COVID-19 infection and 29 after a SARS-CoV-2 vaccine. A total of 13 patients (17.33%) presented AHLE. The moderate form of COVID-19 presented a positive correlation with AHLE (r = 0.691, p < 0.001). The existence of coma and AHLE was correlated with poor outcomes. The following more aggressive immunomodulatory therapies applied in severe cases were correlated with poor outcomes (major sequelae and death): therapeutic plasma exchange (TPE) treatment (r = 382, p = 0.01) and combined therapy with corticosteroids and TPE (r = 0.337, p = 0.03). Conclusions: Vaccinations are essential to reduce the spread of the COVID-19 pandemic, and the monitoring of adverse events is an important part of the strategic fight against SARS-CoV-2. The general benefits and the overall good evolution outweigh the risks, and prompt diagnosis is associated with a better prognosis in these patients.